Age‐related hearing loss: Unraveling the pieces. Issue 2 (21st February 2018) - Tu, Nathan C.; Friedman, Rick A.
Abstract : Age‐related hearing loss (ARHL) is the most common cause of hearing loss in the world. The development of ARHL in each individual is multifactorial, involving both intrinsic and extrinsic factors. This review highlights several of the key findings in the ARHL literature and discusses future directions. Level of Evidence: NA.